1994
DOI: 10.1152/ajpregu.1994.266.4.r1395
|View full text |Cite
|
Sign up to set email alerts
|

Meal patterns of macronutrient intake in rats with particular dietary preferences

Abstract: In the present study, we examined, via computer-assisted analyses, the nocturnal meal patterns of male albino Sprague-Dawley rats with clear differences in their individual preferences for the macronutrients, protein, carbohydrate, and fat. Rats exhibiting a strong preference for the carbohydrate diet over the 12-h nocturnal cycle (approximately 50% of the group) consumed fewer total calories and relatively small, more frequent meals, compared with rats that preferred protein or fat. Moreover, the first meal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…In seeking to identify subtle disturbances in outbred strains before their exhibiting an obese pattern, investigators have taken advantage of the fact that subjects within these populations show considerable variability in their behavioral phenotype and propensity toward obesity. For example, in adult SpragueDawley rats on pure macronutrient or fat-rich diets, measures of weight gain, energy intake or fat preference are found to vary considerably in direct proportion to ultimate body fat accrual, [1][2][3][4][5] with the weight-gain measure providing the basis for selective breeding of rats prone vs resistant to obesity. 6,7 This variability has enabled investigators to identify measures in adult rats, at normal body weight, that can accurately and reproducibly differentiate distinct subgroups that are obesity-prone (OP) or obesity-resistant (OR).…”
Section: Introductionmentioning
confidence: 99%
“…In seeking to identify subtle disturbances in outbred strains before their exhibiting an obese pattern, investigators have taken advantage of the fact that subjects within these populations show considerable variability in their behavioral phenotype and propensity toward obesity. For example, in adult SpragueDawley rats on pure macronutrient or fat-rich diets, measures of weight gain, energy intake or fat preference are found to vary considerably in direct proportion to ultimate body fat accrual, [1][2][3][4][5] with the weight-gain measure providing the basis for selective breeding of rats prone vs resistant to obesity. 6,7 This variability has enabled investigators to identify measures in adult rats, at normal body weight, that can accurately and reproducibly differentiate distinct subgroups that are obesity-prone (OP) or obesity-resistant (OR).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that baseline macronutrient preferences are an important consideration in studies examining the effects of pharmacological or physiological treatments on macronutrient selection (3,13,24,25). The present study was designed to qualify the neuromodulatory effects of GAL and 5 -HT on macronutrient intake in self-selecting rats with macronutrient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was designed to qualify the neuromodulatory effects of GAL and 5 -HT on macronutrient intake in self-selecting rats with macronutrient preferences. There have been a few studies that mention regulation of macronutrient selection or that took macronutrient preferences into account (14,24,26). It has been reported that rats show variation in preferences for specific macronutrients when carbohydrate, protein and fat are offered simultaneously (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the first meal of the feeding cycle has been identified as being the most distinctive in reflecting the individual dietary preferences, that is, rats' mostly consumed the specifie nutrient that was generally preferred over the 24 h cycle during their firs! meal (Shor-Posner et al 1994). Carbohydrate-preferrers consumed fewer total calories and relatively smaller, more frequent meals, compared with rats that preferred protein or fat.…”
Section: Patterns Of Macronutrient Selection and Regulation Of Intakementioning
confidence: 99%